Deep Neural Networks for Automated Image Captioning to Improve Accessibility for Visually Impaired Users - Dongare, Yashwant; Hardas, Bhalchandra M.; Srinivasan, Rashmita; Meshram, Vidula; Aush, Mithun G.; Kulkarni, Atul (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Many researchers are using artificial intelligence and machine learning models to aid the blind due to the advancements in image understanding and automatic image captioning. This research investigates the design and evaluation of deep neural network models for automatic picture captioning, with a focus on improving accessibility for those with visual impairments. The recommended method makes use of deep learning techniques, specifically convolutional neural networks (CNNs) for identifying characteristics in images and recurrent neural networks (RNNs) for generating descriptive captions. The appropriate features are extracted from the input photographs by the CNN and supplied into the RNN so that textual descriptions can be generated. The models are created utilizing techniques like attention processing and beam search to improve the caliber and coherence of the output captions. They are trained using large-scale image caption datasets. Extensive tests are carried out utilizing benchmark datasets as MS COCO and Flickr30k to assess the performance of the created models. The effectiveness of the generated captions is evaluated using objective measures like BLEU, METEOR, and CIDEr. Additionally, a user research with people who are visually impaired is carried out to determine how well the automatic picture captioning system improves accessibility. The outcomes show that the suggested deep neural network models for automatic picture captioning are effective.